Impacts of MDR/XDR-TB on the global tuberculosis epidemic: Challenges and opportunities - Kai Ling Chin; Luis Anibarro; Zi Yuan Chang; Praneetha Palasuberniam; Zainal Arifin Mustapha; Maria E. Sarmiento; Armando Acosta (Current Research in Microbial Sciences)
Tuberculosis (TB) is the world's second-deadliest infectious disease. Despite the availability of drugs to cure TB, control of TB is hampered by the emergence of multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB). The presence of MDR/XDR-TB is alarming due to the low detection rate, high treatment failure, and high mortality. The increasing cases of MDR/XDR-TB are mainly due to the limitations in the diagnostic tests to detect the drug susceptibility of the pathogen, which contribute to the spread of the disease through close contacts. Moreover, inconsistent drug therapy or unsuitable drug regimens could also lead to the subsequent development of drug resistance. The close contacts of an index MDR/XDR-TB patient are at increased risk of developing MDR/XDR-TB. Also, the BCG vaccine may exhibit varying protective effects due to BCG strain diversification, host immune status, exposure to environmental non-tuberculous mycobacteria (NTM), and differences in Mycobacterium tuberculosis (Mtb) subspecies infection, as in the case of sub-optimal protection in the case of Beijing family genotypes of Mtb. This review provides an overview of the current state of drug-resistant tuberculosis (DR-TB) within the context of the global TB pandemic, with a focus on diagnosis, treatment, and the potential impact of BCG vaccination. It highlights the limitations of current approaches and aims to identify opportunities for improving TB control strategies.